Associations of waist-to-height ratio with the incidence of type 2 diabetes and mediation analysis: Two independent cohort studies. Issue 1 (January 2023) - Chen, Ning; Hu, Li-Kun; Sun, Yue; Dong, Jing; Chu, Xi; Lu, Ya-Ke; Liu, Yu-Hong; Ma, Lin-Lin; Yan, Yu-Xiang
Abstract: Aim: To assess the relationship between waist-to-height ratio (WHtR) and the incidence of type 2 diabetes (T2D)/impaired fasting glucose (IFG) and to explore to what extent these associations are mediated by blood pressure, lipids and other indicators related to liver and kidney metabolism. Materials and methods: This study was based on a functional community cohort included 6109 participants which were divided into two sub-cohorts. One sub-cohort included participants with normal fasting glucose (n = 5563), another included IFG individuals at baseline (n = 546). Cox regression models were used to evaluate the relationships of WHtR with T2D/IFG. Four-year time-dependent receiver operating characteristic (ROC) curve and area under curve (AUC) were calculated to estimate the discriminatory power of WhtR and other anthropometric indices on T2D. Mediation analysis was performed to estimate which risk factors mediate the association between WHtR and T2D. Results: Significant positive associations were found between WHtR and the incidence of T2D/IFG in both sub-cohort. WhtR was a useful predictor of T2D ( P < 0.05). Mediation analysis showed that HOMA-IR (0.45 %), SBP (5.10 %), triglycerides (11.02 %), creatinine (9.36 %) and combined kidney indicators (17.48 %) partly mediated the effect of WHtR on T2D in men. For women, this association was partly mediated by SBP (13.86 %), HDL (24.54 %), ALT (6.29 %), UA (22.58 %) and combined kidney indicators (39.51 %). Conclusions: WHtR was an independent risk factor for the development of T2D and IFG. This association was partly mediated by HOMA-IR, SBP, lipids and other liver and kidney metabolism indicators. Highlights: Strong correlations were found between WhtR and T2D/IFG. WhtR was a useful indices in predicting T2D. Association between WHtR and T2D were mediated by HOMA-IR, SBP, lipids and other liver and kidney indicators.